Paxillin-dependent regulation of IGF2 and H19 gene cluster expression - Marášek, Pavel; Dzijak, Rastislav; Studenyak, Irina; Fišerová, Jindřiška; Uličná, Lívia; Novák, Petr; Hozák, Pavel (Journal of cell science, 2015)
Paxillin (PXN) is a focal adhesion protein that has been implicated in signal transduction from the extracellular matrix. Recently, it has been shown to shuttle between the cytoplasm and the nucleus. When inside the nucleus, paxillin promotes cell proliferation. Here, we introduce paxillin as a transcriptional regulator of IGF2 and H19 genes. It does not affect the allelic expression of the two genes; rather, it regulates long-range chromosomal interactions between the IGF2 or H19 promoter and a shared distal enhancer on an active allele. Specifically, paxillin stimulates the interaction between the enhancer and the IGF2 promoter, thus activating IGF2 gene transcription, whereas it restrains the interaction between the enhancer and the H19 promoter, downregulating the H19 gene. We found that paxillin interacts with cohesin and the mediator complex, which have been shown to mediate long-range chromosomal looping. We propose that these interactions occur at the IGF2 and H19 gene cluster and are involved in the formation of loops between the IGF2 and H19 promoters and the enhancer, and thus the expression of the corresponding genes. These observations contribute to a mechanistic explanation of the role of paxillin in proliferation and fetal development.
Keywords: vývoj plodu; signální transdukce; buňky Hep G2; koheziny; genomový imprinting; vývojová regulace genové exprese; fokální adheze; RNA, Long Noncoding; Promoter Regions, Genetic; Signal Transduction; chromozomální proteiny, nehistonové; Focal Adhesions; Enhancer; zesilovače transkripce; Paxillin; Enhancer Elements, Genetic; Cell Proliferation; IGF2; Hep G2 Cells; Extracellular Matrix; Cell Cycle Proteins; Insulin-Like Growth Factor II; Fetal Development; insulinu podobný růstový faktor II; Gene Expression Regulation, Developmental; Cohesin; H19; proteiny buněčného cyklu; paxilin; Humans; metylace DNA; Chromosomal Proteins, Non-Histone; DNA Methylation; promotorové oblasti (genetika); proliferace buněk; RNA dlouhá nekódující; Genomic Imprinting; Imprinting; Cohesins; extracelulární matrix; lidé